Risk and predictive factors of leptospirosis in dogs diagnosed with kidney and/or liver disease in Selangor, Malaysia - Abdul Rahman, Mohammad Sabri; Kuan, Hua Khor; Bejo, Siti Khairani; Seng, Fong Lau; Mazlan, Mazlina; Roslan, Mohd Azri (MDPI AG, 2021)
Canine leptospirosis is commonly associated with kidney and/or liver disease. It has been widely reported and causes public health concerns due to its zoonotic potential and its re-emergence, resulting from close contact between humans and dogs. The current study identified potential risk and predictive factors for dogs diagnosed with kidney and/or liver disease due to leptospirosis. A total of 124 client-owned dogs were recruited, and information such as signalment, medical history, management, and clinical findings were documented. Samples collected from the recruited dogs were directly tested using polymerase chain reaction (PCR) and subsequently inoculated for bacterial isolation. Statistical analyses were descriptively analyzed, and risk analyses were performed using Pearson chi-square tests and logistic regression. A total of 53 dogs (42.7%) were positive for leptospiral infection based on PCR, and 10 leptospiral isolates were successfully recovered from eight dogs. The mortality rate of infected dogs was 34.0% (18/53). Medium and large dog breeds, with a history of exposure to rats, and managed outdoors had a greater risk for leptospirosis (p < 0.05). The significant predictors for the dogs’ positivity were the presence of rats and acute clinical illness (p < 0.05). Administration of antibiotics and the detection of clinical illness at an early stage of the disease improved the survivability of the dogs (p < 0.05). Identifying the profile of dogs that are at risk to leptospirosis could be useful in the design of diagnostic and treatment strategies, as well as to increase awareness for prevention of the disease.